The Effect of “Caregiver Care for Tuberculosis Program” on Improving Knowledge, Attitudes, and Skills in Caring for Children with Tuberculosis - Nursasi, Astuti Yuni; Sartika, Sartika (Faculty of Nursing, Universitas Hasanuddin, 2025)
Aims: This study aimed to evaluate the effect of the Caregiver Care for TB Program on improving the knowledge, attitudes, and caregiving skills of mothers as primary caregivers of children diagnosed with tuberculosis in Depok, Indonesia. Methods: A quasi-experimental study was conducted with 80 mothers divided equally into intervention and control groups. The program included four structured educational sessions delivered in small support groups at a health center over four consecutive weeks. Data were collected at three points: before the intervention (pre-test), immediately after the completion of the sessions (post-test 1), and 10 days after the intervention (post-test 2). Knowledge, attitudes, and skills were measured using the Knowledge, Attitude, and Practice (KAP) questionnaire for Tuberculosis care. Results: Significant improvements were observed in the intervention group compared to the control group in knowledge (p=0.000) and attitudes (p=0.000) and skills (p=0.000), as well as improvements in knowledge, attitude, and skills 10 days later (p < 0.000). Conclusion: The Caregiver Care for TB Program effectively enhanced caregivers' knowledge, attitudes, and caregiving skills in preventing TB transmission among children. This program should be implemented as part of TB control strategies in high-burden areas